Examination of Trend and Patterns of Rainfall and Temperature in Awka, Anambra State (1975 – 2020) (Journal of Geography, Meteorology and Environment, 2022)
The study examined the trend and patterns of rainfall and temperature in Awka, Anambra State from 1975-2020. The study used long term historical data on rainfall, minimum and maximum air temperature to investigate observed climatic variability. Monthly rainfall, minimum and maximum temperature data were obtained from the Nigerian Meteorological Agency (NIMET), Abuja. The study usedMann–Kendall and Sen’s slope estimator tests to detect monotonic trends in the mean annual and total rainfall, minimum, maximum and mean temperature and their magnitude with MAKESENS_1_0 application in EXCEL format. The result indicated an increasing trend in rainfall and temperature in the area. Rainfall pattern was characterized in terms of standardized anomaly index and seasonality index while temperature was characterized in terms of anomaly index. The result of rainfall seasonality index showed that annual rainfall has witnessed a shift from months to extreme seasonality. The rainfall and temperature standardized anomaly index showed that rainfall fluctuated in the area from dry and wet years. The maximum Standardized Rainfall Anomaly Index (SRAI) was 3.460 in 2019 indicating an extremely wet year while the minimum SRAI was -1.241 indicating moderately dry year. The maximum Seasonality Index(SI) was 1.5311 indicating an almost all rain in 1- 2 months while the minimum SI was 0.4256 indicating rather seasonal rainfall with a short drier season.
Keywords: Anomaly index; Climate Change; Rainfall; Seasonality index; Temperature; Trend analysis